The relationship between emotional intelligence and academic performance of chartered accountancy students at a south African tertiary institution - Magaya, Sinazo (College of Accounting, 2024)
The concept of emotional intelligence (EI) is gaining traction in academia and in recruitment spaces. In education, studies conducted outside South Africa suggest that a relationship exists between EI and the academic performance of students. The purpose of this study was to assess whether a relationship exists between the EI of undergraduate accounting students registered at a South African tertiary institution and their academic performance. A quantitative research approach was applied and 103 students completed a questionnaire that was used to measure their EI. The mean EI score was ‘average' at 172 points per the NHS EI measurement toolkit scores. Academic performance data was obtained for each study participant. The average mark was 73% and the average pass rate was 99%. Regression analysis was conducted to assess the relationship between the measure of EI and students' academic performance. The results revealed a negative relationship between overall EI and academic performance. This relationship was however not statistically significant as the P-value was larger than the significance level (α = 0.05) at 0.1. A negative relationship was also noted between individual EI elements and academic performance. Therefore, EI is not seen as one of the factors that affect academic performance of South African accounting students at an undergraduate level. This paper contributes to the ongoing research on factors that affect academic performance of South African accounting students, in an attempt to improve success rates in accounting studies.